A new zooarchaeological application for geometric morphometric methods: Distinguishing Ovis aries morphotypes to address connectivity and mobility of prehistoric Central Asian pastoralists. (July 2019) - Haruda, A.F.; Varfolomeev, V.; Goriachev, A.; Yermolayeva, A.; Outram, A.K.
Abstract: Geometric morphometric methods (GMM), which were developed to characterize the shape and size of biological organisms, have been applied within zooarchaeology over the past decade to address animal domestication processes and to refine morphological criteria to differentiate between taxa. However, there has been limited utilization of these methods to discriminate between populations of the same taxa to challenge and refine other key archaeological issues, such as migration and connectivity in prehistory. Presented here is a novel application of a three-dimensional landmark based geometric morphometric approach to address the nature of long distance trade and connectivity on the prehistoric Silk Road. The similarity of Bronze and Iron Age archaeological cultures along this steppe route has encouraged characterisations of these people as nomads, with highly mobile, integrated, and connected human and animal populations. However, the interconnectedness of domestic animal populations, in particular sheep ( Ovis aries), the foundation of this prehistoric pastoral economy, has never been examined. This study utilized geometric morphometric methods to quantify geometric morphometric variance of O. aries astragali between three geographically disparate settlement sites within a single Final Bronze age cultural and chronological context. Significant differences between morphotypes revealed that protracted mobility patterns were unlikely and that while animal exchange may have occurred, it was not pervasive enough to produce a uniform sheep morphotype across central and southeastern Kazakhstan. The result of this new application of geometric morphometric methods challenges models of uniform and undifferentiated long distance mobility and economic connectivity between the peoples of the Silk Road. Highlights: Geometric morphometric methods are robust for zooarchaeological postcranial data. The morphology of O. aries astragali can discriminate between populations. There was no exchange of sheep along the prehistoric Silk Road in Central Asia.